Effects of in-season short-term plyometric training program on sprint and jump performance of young male track athletes - Chelly, M. S.; Hermassi, S.; Shephard, R. J. (The Journal of Strength and Conditioning Research, 2015)
We studied the effect of supplementing normal in-season training by a 10-week lower limb plyometric training program (hurdle and depth jumping), examining measures of competitive potential (peak power output [PP], sprint running velocity, squat jump [SJ], countermovement jump [CMJ], drop jump [DJ], and lower limb muscle volume). The subjects (27 male track athletes, aged 11.9 ± 1.0 years; body mass: 39.1 ± 6.1 kg; height: 1.56 ± 0.02 m; body fat: 12.8 ± 4.4%) were randomly assigned between a control (normal training) group (C; n = 13) and an experimental group (E; n = 14) who also performed plyometric training 3 times per week. A force-velocity ergometer test determined PP and SJ, and an Optojump apparatus evaluated CMJ height and DJ (height and power). A multiple-5-bound test assessed horizontal jumping, and video-camera analyses over a 40-m sprint yielded velocities for the first step (VS), the first 5 m (V5m), and between 35 and 40 m (Vmax). Leg muscle volume was estimated anthropometrically. Experimental group showed gains relative to C in SJ height (p < 0.001); CMJ height (p < 0.01); DJ height and power relative to body mass (p < 0.01 for both); and all sprint velocities (p < 0.01 for VS and V5m, p = 0.05 for Vmax). There was also a significant increase (p < 0.01) in thigh muscle volume, but leg muscle volume, thigh cross-sectional area, and PP remained unchanged. We conclude that adding plyometric training improved important components of athletic performance relative to standard in-season training in young runners.